Experimental investigation of evacuated heat pipe solar collector efficiency using phase-change fluid - Fang, Wenbo; Riffat, Saffa; Wu, Yupeng (Oxford University Press, 2017)
Performance of a microencapsulated phase-change material (PCM) as a heat-transport medium in an evacuated heat pipe solar collector was evaluated and the results compared with those using water. Collector efficiency was experimentally determined according to the method based on European Standard EN 12975–2:2006. This method proved unsuitable when using an encapsulated PCM suspension. A modified test method was proposed, which was appropriate for predicting solar collector efficiency when using a phase-change fluid. Average solar collection efficiency when using a PCM suspension was higher than that using water.